Liver splitting during normothermic machine perfusion: a novel method to combine the advantages of both in-situ and ex-vivo techniques. Issue 5 (May 2023) - Lau, Ngee-Soon; Ly, Mark; Dennis, Claude; Ewenson, Kasper; Ly, Hayden; Huang, Joanna L.; Cabanes-Creus, Marti; Chanda, Sumon; Wang, Chuanmin; Lisowski, Leszek; Liu, Ken; Kench, James; et al.
Abstract: Background: Split liver transplantation permits the transplant of two recipients using a single donor liver. Liver splitting can be performed using the ex-vivo technique (more convenient), or the in-situ technique (shorter cold ischaemic time). We aimed to develop a technique for liver splitting during normothermic machine perfusion which combines the advantages of both techniques and permits graft assessment prior to transplant. Methods: Human livers declined for transplantation were perfused at 36 °C using a modified-commercial perfusion machine. We developed a six-step method to split whole livers into left lateral segment grafts and extended right grafts. Both partial livers were then perfused on separate machines for individual assessment. Results: Using our technique, 10 whole livers were successfully split during normothermic perfusion resulting in 20 partial grafts. Apart from a single graft which failed due to a technical error, all grafts survived for 24-h after splitting. Survival was demonstrated by lactate clearance, bile production and synthesis of coagulation factors. Conclusions: Liver splitting during normothermic machine perfusion has the potential to revolutionise split liver transplantation. We describe a novel technique that reliably achieves two grafts from a single donor liver. This raises the possibility of semi-elective transplantation, and sophisticated graft assessment prior to implant.